Measuring lunchtime consumption in school cafeterias: a validation study of the use of digital photography. Issue 10 (4th April 2019) - Marcano-Olivier, Mariel; Erjavec, Mihela; Horne, Pauline J; Viktor, Simon; Pearson, Ruth
Abstract: Objective: The present study tested the validity of a digital image-capture measure of food consumption suitable for use in busy school cafeterias. Design: Lunches were photographed pre- and post-consumption, and food items were weighed pre- and post-consumption for comparison. Setting: A small research team recorded children's lunchtime consumption in one primary and one secondary school over seven working days. Participants: A primary-school sample of 121 children from North Wales and a secondary-school sample of 124 children from the West Midlands, UK, were utilised. Nineteen children were excluded because of incomplete data, leaving a final sample of 239 participants. Results: Results indicated that (i) consumption estimates based on images were accurate, yielding only small differences between the weight- and image-based judgements (median bias=0·15–1·64 g, equating to 0·45–3·42 % of consumed weight) and (ii) good levels of inter-rater agreement were achieved, ranging from moderate to near perfect (Cohen's κ =0·535–0·819). This confirmed that consumption estimates derived from digital images were accurate and could be used in lieu of objective weighed measures. Conclusions: Our protocol minimised disruption to daily lunchtime routine, kept the attrition low, and enabled better agreement between measures and raters than was the case in the existing literature. Accurate measurements are a necessary tool for all those engaged in nutrition research, intervention evaluation, prevention and public health work. We conclude that our simple and practical method of assessment could be used with children across a range of settings, ages and lunch types.